2015
DOI: 10.1093/humrep/dev005
|View full text |Cite
|
Sign up to set email alerts
|

The expression of microRNA-451 in human endometriotic lesions is inversely related to that of macrophage migration inhibitory factor (MIF) and regulates MIF expression and modulation of epithelial cell survival

Abstract: This study was funded by the National Institutes of Health/NICHD by grant NIH HD069043 to W.B.N. The authors have no competing interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 46 publications
6
53
1
Order By: Relevance
“…Non-neuronal TRPV1 can also be activated by the endocannabinoid anandamide in the rat reproductive system (Cella et al 2008, Scotchie et al 2014. These results are consistent with increased TRPA1 and TRPV1 expression in rat and human endometriosis demonstrated by our laboratory (unpublished results) and literature data (Hucho & Levine 2007, Ilie & Ilie 2013, Graham et al 2015. Increased estrogen synthesis in endometriosis lesions makes those results comparable to these data.…”
Section: Discussionsupporting
confidence: 87%
“…Non-neuronal TRPV1 can also be activated by the endocannabinoid anandamide in the rat reproductive system (Cella et al 2008, Scotchie et al 2014. These results are consistent with increased TRPA1 and TRPV1 expression in rat and human endometriosis demonstrated by our laboratory (unpublished results) and literature data (Hucho & Levine 2007, Ilie & Ilie 2013, Graham et al 2015. Increased estrogen synthesis in endometriosis lesions makes those results comparable to these data.…”
Section: Discussionsupporting
confidence: 87%
“…Lastly, overexpression of miR-451 in an immortalized human endometriotic epithelial cell line (12Z) led to the decreased expression of its target YWHAZ which was correlated with decreased cell proliferation. Collectively, both our study 46 and that of Joshi and colleagues 47 demonstrated that miR-451 is capable of modulating cell proliferation and this is associated with alterations in the expression of targets MIF and YWHAZ.…”
Section: Putative Targets Of and Functions For Specific Mirnas In Esupporting
confidence: 62%
“…Our laboratory reported the initial study examining both miR451 expression and function in human tissue and cells. 46 miR-451 is elevated in endometriotic lesion tissue compared with paired eutopic endometrium from women with the disease. 24 miR-451 expression exhibited an inverse association with transcript and protein expression of putative target, macrophage migration inhibitory factor (MIF).…”
Section: Putative Targets Of and Functions For Specific Mirnas In Ementioning
confidence: 94%
“…1C). Regarding miR-451a, Graham's team has recently published two studies showing increased levels of this miRNA in ovarian endometriomas that correlate with lesion size and with its serum levels (30,31). Provided that PF is mainly composed of blood components (32), and usually up-regulated proteins in serum are proportionally up-regulated in PF (33), our results are in accordance with Graham's, suggesting an important role for miR-451a as a mediator of inflammation in the peritoneal microenvironment.…”
Section: Discussionmentioning
confidence: 99%